Development of models and assessment of the world walnut variety fund by fruit quality - S. G. Biganova; Yu. I. Sukhorukikh; A. P. Glinushkin; E. K. Pchikhachev (Новые технологии)
Walnut (Juglans regia L.) is a particularly significant plant for humans in terms of its useful properties and in the Russian Federation it can be attributed to the most valuable introducers for forestry and horticulture. It is grown in many countries of the world and the area of its cultivation is constantly expanding. Breeding species for food purposes requires a selection assessment of the quality of its fruits. For this, at different times, appropriate methods were developed and the existing gene pool of the culture was assessed. By now, new varieties and forms have been bred and brought, which also need to be evaluated for rational use for scientific and practical purposes. The descriptions of varieties and forms of walnut often contain insufficient information about all selected traits, which requires the development of new models to assess the variety fund using incomplete data. The purpose of the research is to develop the missing models of selection evaluation using incomplete data and evaluate the world walnut variety fund in terms of fruit quality, to identify varieties and forms of the highest quality category. The well-known methodology and new models have been used for the evaluation. When developing evaluation models for incomplete data, a database of 50 varieties evaluated for all indicators has been used. Using the method of excluding individual indicators, the corresponding multiple regression models have been calculated on its basis, taking into account a different combination of features. The licensed programs Stadia 8.0, Microsoft Excel have been used in the research. The proposed models provide an estimate with an average error of ± 0.48 – 3.72 points at R2 = 0.63 – 0.99. A promising walnut gene pool from 23 countries has been assessed, 69 representatives with fruits of the breeding category of the highest quality identified, and a list of them compiled. Of the 512 ancestors, 19.73% had the selection category of fruits of the highest quality, 62.88% of high-quality fruits, 16.80% of ordinary fruits, and 0.59% of varieties and forms of low-quality fruits.